Mekanisme Transformasi Digital Dalam Proses Lelang: Komparasi Antara Sistem Lelang Konvensional Dan Sistem Lelang Elektronik Pada Kantor Pelayanan Kekayaan Negara Dan Lelang (KPKNL) Kota Mataram - Ikhram, Orysa Sativa; Priyambodo, Victoria Kusumaningtyas (Fakultas Ekonomi dan Bisnis Unram, 2025)
Digital transformation has become a major focus in improving efficiency and transparency in various aspects of public administration, including the auction process. In the Mataram City State Asset and Auction Service Office (KPKNL), the use of conventional systems has long been the main method in organizing auctions. However, with the development of technology, electronic systems have begun to be introduced to assist or complement conventional systems. This study aims to see the mechanism of digital transformation in the auction process where conventional and electronic systems are used simultaneously in the Mataram City State Asset and Auction Service Office (KPKNL). The author uses a comparative method to evaluate the differences in terms of speed, transparency, and accuracy between the two systems. Conventional systems that involve paper-based auction processes and direct interaction often face challenges related to speed and the risk of human error. In contrast, electronic systems offer advantages in terms of automation, accessibility, and reduced potential for fraud. The results of this study are expected to provide useful insights for government agencies and related institutions in designing policies that support more effective digital transformation in the auction process, especially in the Mataram City State Asset and Auction Service Office (KPKNL).